A corte dos reis do Congo e os maracatus do Recife - Silva, Leonardo Dantas (Ciência & Trópico, 2011)
RESUMOTrata da origem do maracatu pernambucano, para a qual contribui a paulatina transformação dos antigos e coloniais cortejos dos reis do Congo. Centra suas reflexões a partir das observações do jornal pernambucano O Carapuceiro, publicado, no século XIX, pelo Padre Miguel do Sacramento Lopes Gama.ABSTRACTThe “Kings of the Congo Court” and the “maracatus” of Recife. v. 27, n. 2, p. 363-384, jul./dez. 1999.Studies the origins of the “maracatu” (carnival folk dance group) of Pernambuco (State of the Northeast of Brazil), arguing that it is the result of the changes in the old colonial “cortejos dos reis do Congo” (Kings of the Congo processions). Concentrates the analysis of the subject matter mostly on the stories of the 1900th century newspaper of Pernambuco O Carapuceiro, created and runned by the catholic priest Miguel do Sacramento Lopes Gama.RÉSUMÉLa cour des rois du Congo et les “maracatus” de Recife. v. 27, n. 2, p. 363-384, jul./dez. 1999.L’auteur traite de l’origine du “maracatu” dans le Pernambouc à laquelle a contribué la lente transformation des anciens cortèges des rois du Congo de l’époque coloniale. Il centre ses réfléxions à partir des observations du journal pernamboucain “ O Carapuceiro”, publié au XIX e siècle par le Père Miguel do Sacramento Lopes Gama.